(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article examines scientific approaches to the impact of digital transformation on innovation and investment development of entrepreneurship. Scientific approaches to the definition of digital transformation of innovative and investment development of entrepreneurship are considered. It is well-founded that the digital economy is characterized by rapid technological changes, new business models, and the growing importance of data and information technologies. As a result of its existence, new opportunities for innovations appear, which require their adequate implementation and timely commercialization by entrepreneurs. It is proposed to take into account not only the ability of entrepreneurial structures to use such technologies in their activities (an investment component of digital transformation), but also to consider these technologies simultaneously as a result of entrepreneurship - the development of digital technologies, their constant modernization and improvement (an innovative component of digital transformation). The key role of the analysis of the current state of digitalization, the determination of such key indicators as Internet penetration, the level of automation and the use of cloud technologies is highlighted, and a comparison of these indicators with international ratings is made. It has been found that the transformation under the influence of digital technologies changes the understanding of the nature of entrepreneurship, which is caused by a number of factors that can influence both the development of digital technologies in general and the ability to implement them in business models, that is, it covers the processes of innovation and investment development of the economy. It is important to identify the key sectors of the economy that have the greatest impact on GDP and employment, and to assess the potential for investment in each of these sectors. It is also important to assess the impact of digitalization on the effectiveness of investments using econometric models to measure the return on investment, as well as to analyze successful cases of digitalization both in Ukraine and abroad, to identify risks and barriers related to digitalization, and to develop strategies to overcome them .